Study guides

Q: 5m² - 29 If m equals 2?

Write your answer...

Submit

Related questions

m = -1

5m - 5 + 2 = 1 Therefore, 5m - 3 = 1 5m = 4 m = 4/5 m = 0.8

5m-7m = 12 -2m = 12 -2m/-2 = 12/-2 m = -6

2 - 7n = 6therefore 7n = 2 - 6 = -4 and so n = -4/7 Then 5m + 7n = 6.4 becomes 5m - 4 = 6.4 so that 5m = 10.4 and then m = 10.4/5 = 2.08

m = 8

m = 4

-5m-3+4 = 11 -5m = 11+3-4 -5m = 10 m = -2

3+4m+5m=214m+5m=21-39m=18m=18/9m=2

m = 4

40

5m is the same as 5 x mIf m = 6...5 x 6 = 30

5m=40/5=/5m=8

8.04 m - 5.80 m = 2.24 m or 2m 24 cm

-3m = 5m+8 -3m-5m = 8 -8m = 8 m = -1

5m+3=3m+9 5m+3-3=3m+9-3 5m=3m+6 5m-3m=3m+6-3m 2m=6 (2m)/2=6/2 m=3

4m+9+5m-12=42 9m=45 m=5

Assuming -5m=11:Divide both sides by -5: m= -11/5And you have what m equals.

5m = 40m = 40/5m = 8

5m=3 therefore m =3 over 5

m2 - 5m - 14 = 0(m - 7) (m + 2) = 0The equation is true ifm = 7orm = -2

cheese cake

M = 5 * * * * * 4m + m - 11 = 9 or 5m - 11 = 9 so that 5m = 20 and then m = 4, NOT 5.

5m2 - 17m + 12 = 0âˆ´ 5m2 - 5m - 12m + 12 = 0âˆ´ 5m(m - 1) - 12(m - 1) = 0âˆ´ (5m - 12)(m - 1) = 0âˆ´ m âˆˆ {1, 12/5}

5m = 2m - 153m = -15m = -15/3m = -5

30 m^2